The Roots of Verbal Meaning - Beavers , John (Oxford Studies in Theoretical Linguistics, 2020)
This book explores possible and impossible word meanings, with a specific focus on the meanings of verbs. It adopts the now common view that verb meanings consist at least partly of an event structure, made up of an event template describing the verb's broad temporal and causal contours that occurs across lots of verbs and groups them into semantic and grammatical classes, plus an idiosyncratic root describing specific, real world states and actions that distinguish verbs with the same template. While much work has focused on templates, less work has addressed the truth conditional contributions of roots, despite the importance of a theory of root meaning in fully defining the predictions event structural approaches make. This book addresses this lacuna, exploring two previously proposed constraints on root meaning: The Bifurcation Thesis of Roots, whereby roots never introduce the meanings introduced by templates, and Manner/Result Complementarity, which has as a component that roots can describe either a manner or a result state but never both at the same time. Two extended case studies, on change-of-state verbs and ditransitive verbs of caused possession, show that neither hypothesis holds, and that ultimately there may be no constraints on what a root can mean. Nonetheless, the book argues that event structures still have predictive value, and it presents a new theory of possible root meanings and how they interact with event templates that produces a new typology of possible verbs, albeit one where not just templates but also roots determine systematic semantic and grammatical properties.